PERANCANGAN RUMAH SUSUN HIJAU DI CENGKARENG DENGAN PENDEKATAN RETHINKING TYPOLOGY DAN TRANSPROGRAMMING - Alexander Jason; Nina Carina (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Jakarta is a city with a very high population density. Every year the population in Jakarta increases by around 88 thousand people according to the Central Statistics Agency for the Special Capital Region of Jakarta in 2020. This is partly due to the high level of urbanization. The high urbanization resulted in the increasing demand for housing. However, the limited amount of land has resulted in higher land prices while the purchasing power of most people for housing in Jakarta has decreased and has led to the emergence of slums. The bad impact of living in slums is the weakening in the quality of health which has a direct impact on the weakening in the standard of living of its inhabitants. Therefore, it is needed flats that not only deal with the problem of slum settlements but also deal with health and economic problems of the residents of the flats so that the standard of living of the community is increasing and has a healthy living environment. The concept of this project is housing that is able to accommodate the lives of Low-Income Communities. This project is a new solution for livable housing that is able to improve the welfare of Low-Income Communities through the main housing program as well as supporting programs for planting areas and independent markets. Residents are expected to be able to live and work in a healthy environment. The design approach uses "Rethinking Typology" which pays attention to aspects of spatial form/configuration, function, and image in a dwelling and the relationship between concepts and program contexts in buildings. Keywords:  housing; rethinking typology; slum settlement AbstrakJakarta merupakan kota dengan tingkat kepadatan penduduk sangat tinggi. Setiap tahun penduduk di Jakarta bertambah sekitar 88 ribu jiwa menurut Badan Pusat Statistik (BPS) Daerah Khusus Ibukota (DKI) Jakarta tahun 2020. Hal ini antara lain disebabkan tingkat urbanisasi yang tinggi. Tingginya urbanisasi mengakibatkan bertambahnya kebutuhan akan perumahan. Namun jumlah lahan yang terbatas mengakibatkan harga lahan semakin tinggi sementara kemampuan daya beli sebagian besar masyarakat untuk hunian di Jakarta semakin menurun dan menjadikan timbulnya permukiman kumuh. Dampak buruk dari bermukim di permukiman kumuh adalah menurunnya kualitas kesehatan yang berdampak langsung pada turunnya taraf kehidupan penghuninya. Oleh karena itu dibutuhkan hunian susun yang bukan hanya menangani masalah permukiman kumuh tetapi juga menangani masalah kesehatan dan perekonomian para penghuni rumah susun tersebut agar taraf kehidupan masyarakat semakin meningkat dan mempunyai lingkungan hidup yang sehat. Konsep proyek ini adalah hunian yang mampu mengakomodasi kehidupan Masyarakat Berpenghasilan Rendah (MBR). Proyek ini adalah solusi baru hunian layak huni yang mampu meningkatkan kesejahteraan MBR melalui  program utama  hunian serta program pendukung area tanam dan pasar mandiri. Penghuni diharapkan dapat bermukim sekaligus bekerja di dalam lingkungan yang sehat. Pendekatan perancangan menggunakan “Rethinking Typology” yang memperhatikan aspek bentuk/konfigurasi spasial, fungsi dan citra dalam suatu hunian dan hubungan antara konsep dan konteks program dalam bangunan.